Accuracy of capturing nasal, orbital, and auricular defects with extra- and intraoral optical scanners and smartphone: An in vitro study. (February 2022) - Unkovskiy, Alexey; Spintzyk, Sebastian; Beuer, Florian; Huettig, Fabian; Röhler, Ariadne; Kraemer-Fernandez, Pablo
Abstract: Objectives: This in vitro study compares the scanning accuracy of various stationary and portable as well as extra- and intraoral devices for capturing oncological defects. Methods: A 3D-printed model of a nasal, orbital, and auricular defect, as well as one of an intact auricle, were digitalized ( n = 7 per device) with a stationary optical scanner (Pritiface), a portable extraoral optical scanner (Artec Space Spider), two intraoral scanners (Trios 4 and Primescan), and a smartphone (iPhone 11 Pro). For the reference data, the defect models were digitalized using a laboratory scanner (D2000). For quantitative analysis, the root mean square error value for trueness and precision and mean deviations in millimeters were obtained for each defect type. The data were statistically analyzed using two-way ANOVA and Tukey multiple comparison test. For qualitative analysis, a colorimetric map was generated to display the deviation within the defect area and adjacent tissue. Results: Statistically significant interactions were found in the trueness and precision for defect and scanner type. Conclusion: The Primescan and Artec Space Spider scanners showed the highest accuracy for most defect types. Primescan and Trios 4 failed to capture the orbital defect. The iPhone 11 Pro showed clinically acceptable trueness but inferior precision. Clinical significance: The scanning devices may demonstrate varying accuracy, depending on the defect type. A portable extraoral optical scanner is an universal tool for the digitization of oncological defects. Alternatively, an intraoral scanner may be employed in maxillofacial prosthetics with some restrictions. Utilizing a smartphone in maxillofacial rehabilitation should be considered with caution, because it provides inconsistent accuracy.